PERAN IT ETHICS AND REGULATION DALAM MENINGKATKAN EFEKTIVITAS CYBERSECURITY DI ERA TEKNOLOGI - Firmansyah, Ricky (STMIK KAPUTAMA, 2025)
Cybersecurity, IT ethics, and regulations are three crucial elements in establishing a secure digital environment in the technological era. The rising frequency of cyberattacks and data breaches poses significant challenges that demand a holistic approach integrating responsive regulations and robust ethical practices. Based on a literature review, theories such as the Confidentiality, Integrity, and Availability (CIA) model and ethical principles like utilitarianism and deontology form the foundation of this analysis. This study employs a literature review methodology with thematic analysis of journals and regulatory documents. Data were collected through systematic searches in academic databases to identify patterns, themes, and key relationships. The findings reveal that while regulations like the GDPR serve as strong examples, significant challenges persist in global harmonization and local implementation. Additionally, a lack of digital literacy and ethical awareness at both individual and organizational levels hampers efforts to enhance cybersecurity. By integrating regulatory, ethical, and technological aspects, this research provides a holistic perspective on how these three elements can collaboratively address the challenges of digital security in the future.